Consolidation of Aniops Casey, Psiona Casey, Preglyptobaris Bondar and Prospoliata Hustache with Chryasus Champion (Coleoptera, Curculionidae, Baridinae) and descriptions of new species - Prena, Jens (Zootaxa, 2024)
Aniops Casey, 1922, Psiona Casey, 1922, Preglyptobaris Bondar, 1946 and Prospoliata Hustache, 1950 are here proposed as new junior synonyms of Chryasus Champion, 1908 because their ostensibly diagnostic character states are more or less continuous following examination of numerous species from throughout their geographic ranges and are not valid as separate lineages in this broader context. Amphibaris bruniceps Bondar, 1946, Aniops sculpturatus Casey, 1922, Baris multistriata Chevrolat, 1880, Preglyptobaris bicolor Bondar, 1946, Psiona carinulosa Casey, 1922 and Psiona densa Casey, 1922 are transferred to Chryasus (new combinations). Baridius ignavus Boheman, 1844 and Amphibaris dispar Bondar, 1946 are transferred from Sphenobaris Champion, 1909 to Glyptobaris Casey, 1892 (new combinations). Prospoliata bicolorata Hustache, 1950 is a new junior synonym of Preglyptobaris bicolor Bondar, 1946 and Psiona opaca Casey, 1922 is a new junior synonym of Psiona densa Casey, 1922. Ten new species are described: C. bicuspis Prena new species (Ecuador), C. clunis Prena new species, C. macer Prena new species, C. montyi Prena new species, C. nimius Prena new species (all Costa Rica), C. persimilis Prena new species (Costa Rica, Panamá), C. pomponella Prena new species (Perú), C. taironius Prena new species (Colombia), C. talamanca Prena new species (Panamá) and C. wappesi Prena new species (French Guiana, Venezuela). These actions increase the number of included species from two to eighteen. They occur from México to Brazil and in the Lesser Antilles. Two species induce and develop in elongate galls in leaf petioles of Miconia pittieri Cogn. and M. prasina (Sw.) DC (Melastomataceae), respectively. Several others with unknown biology were collected from the same plant genus or unidentified Melastomataceae.